A strategy for improving the motivation and mental health of adolescents, based on Javanese local wisdom - Setiyarini, Hening; Fauzi, Alisya Zahira; AtsTsaqofi, Nadzira Atalla Muthi’; Wijayanti, Zaqiyah; Ramadani, Isna Okta; Salim, Agus (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Adolescents are an age group vulnerable to mental health problems. According to the 2022 Indonesia National Adolescent Mental Health Survey (I-NAMHS), 34.9% of Indonesian adolescents experienced mental health problems in the past 12 months, with anxiety being the most common disorder. Purpose: To examine the relationship between the understanding of the Javanese philosophy Urip Iku Urup and adolescents’ motivation and mental health. Method: A quantitative correlational design with 163 adolescents aged 15–19 years from SMK Negeri 1 Cangkringan, Sleman Regency, Special Region of Yogyakarta, selected using purposive sampling. The instruments used were a motivation scale based on Maslow’s theory and a mental health scale based on Viktor Frankl’s logotherapy. Results: Assumption testing showed that the data were normally distributed (p > 0.05) and linear (p < 0.05). Reliability analysis indicated Cronbach’s Alpha of 0.909 for the mental health scale and 0.952 for the motivation scale, both of which are categorized as very high. Hypothesis testing using Pearson Product Moment correlation revealed a very strong and significant positive relationship between the understanding of Urip Iku Urup philosophy and adolescents’ motivation and mental health (r = 0.841; p = 0.000). Conclusion: These findings demonstrate that local cultural values can serve as preventive and promotive strategies for enhancing adolescents’ motivation and mental health. Keywords: Adolescents; Local Wisdom; Mental Health; Motivation.